Comparison of two different Ecarin Clotting Time methods - Fenyvesi, Tivadar; Harenberg, Job; Weiß, Christel; Jörg, Ingrid (Journal of thrombosis and thrombolysis, 2005)
Background: Ecarin Clotting Time (ECT) assay specifically determines the inhibition of meizothrombin by direct thrombin inhibitors (DTI). Blood coagulation factor levels lowered by vitamin K antagonists (VKA) may prolong ECT. Concomitant treatment of VKA with DTI may influence differently the two published ECT methods.
Gesehen am 20.04.2022